Tissue Distribution of Kir7.1 Inwardly Rectifying K+ Channel Probed in a Knock-in Mouse Expressing a Haemagglutinin-Tagged Protein - Cornejo, Isabel; Villanueva, Sandra; Burgos, Johanna; López-Cayuqueo, Karen I.; Chambrey, Régine; Julio-Kalajzić, Francisca; Buelvas, Neudo; Niemeyer, María I.; Figueiras-Fierro, Dulce; Brown, Peter D.; Sepúlveda, Francisco V.; Cid, L. P. (Frontiers in Physiology, 2018)
Kir7.1 encoded by the Kcnj13 gene in the mouse is an inwardly rectifying K+ channel present in epithelia where it shares membrane localization with the Na+/K+-pump. Further investigations of the localisation and function of Kir7.1 would benefit from the availability of a knockout mouse, but perinatal mortality attributed to cleft palate in the neonate has thwarted this research. To facilitate localisation studies we now use CRISPR/Cas9 technology to generate a knock-in mouse, the Kir7.1-HA, that expresses the channel tagged with a haemagglutinin (HA) epitope. The availability of antibodies for the HA epitope allows for application of western blot and immunolocalisation methods using widely available anti-HA antibodies with WT tissues providing unambiguous negative control. We demonstrate that Kir7.1-HA cloned from the choroid plexus of the knock-in mouse has the electrophysiological properties of the native channel, including large Rb+ currents characteristic of the native channel. These large Kir7.1-mediated currents are accompanied by abundant apical membrane Kir7.1-HA immunoreactivity. WT-controlled western blots demonstrate the presence of Kir7.1-HA in the eye and the choroid plexus, trachea and lung, and intestinal epithelium but exclusively in the ileum. In the kidney, and at variance with previous reports in the rat and guinea-pig, Kir7.1-HA is expressed in the inner medulla but not in the cortex or outer medulla. In isolated tubules immunoreactivity was associated with inner medulla collecting ducts but not thin limbs of the loop of Henle. Kir7.1-HA shows basolateral expression in the respiratory tract epithelium from trachea to bronchioli. The channel also appears basolateral in the epithelium of the nasal cavity and nasopharynx in newborn animals. We show that HA-tagged Kir7.1 channel introduced in the mouse by a knock-in procedure has functional properties similar to the native protein and the animal thus generated has clear advantages in localisation studies. It might therefore become a useful tool to unravel Kir7.1 function in the different organs where it is expressed.